Interleukin-6 and C-Reactive Protein Are Overexpressed in the Liver of Perinatal Deaths Diagnosed with Fetal Inflammatory Response Syndrome. (2nd January 2014) - Pereira, Lívia Helena M.; Machado, Juliana R.; Olegário, Janaínna G. P.; Rocha, Laura P.; Silva, Marcos V.; Guimarães, Camila S. O.; Reis, Marlene A.; Castellano, Lúcio Roberto; Ramalho, Fernando S.; Corrêa, Rosana R. M.
Abstract : Anatomopathologic studies have failed to define the fetal inflammatory response syndrome (FIRS) as a cause of fetal death. Here, liver fragments of perinatal autopsies were collected at a university hospital from 1990 to 2009 and classified according to the cause of death, perinatal stress, and gestational age (GA) of the fetus. IL-6, TNF- α, and C-reactive protein (CRP) expression were immunostained, respectively, with primary antibody. Cases with congenital malformation, ascending infection, and perinatal anoxia showed increased IL-6, CRP, and TNF- α, respectively. Prematures presented higher expression of IL-6 whereas term births showed higher expression of CRP. Cases classified as acute stress presented higher expression of IL-6 and TNF- α and cases with chronic stress presented higher expression of CRP. GA correlated negatively with IL-6 and positively with CRP and TNF- α . Body weight correlated negatively with IL-6 and positively with CRP and TNF- α . Despite the diagnosis of FIRS being clinical and based on serum parameters, the findings in the current study allow the inference of FIRS diagnosis in the autopsied infants, based on an in situ liver analysis of these markers.